Spread and Liquidity Issues: A markets comparison - Sebastjan Strašek; Bor Bricelj (Naše gospodarstvo/Our economy, 2016)
The financial crises are closely connected with spread changes and liquidity issues. After defining and addressing spread considerations, we research in this paper the topic of liquidity issues in times of economic crisis. We analyse the liquidity effects as recorded on spreads of securities from different markets. We stipulate that higher international risk aversion in times of financial crises coincides with widening security spreads. The paper then introduces liquidity as a risk factor into the standard value-at-risk framework, using GARCH methodology. The comparison of results of these models suggests that the size of the tested markets does not have a strong effect on the models. Thus, we find that spread analysis is an appropriate tool for analysing liquidity issues during a financial crisis.